System for PID Control and Autotuning PID using Ziegler-Nichols Method - Yash Mewada; Sarvesh Prajapati; Raj Hakani (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
The impact of automation had drawn our attention towards the advancements of closed-loop control systems (feedback/feedforward control systems). A PID control system is used in almost every industrial as well as commercial application. Therefore, it becomes important to efficiently tune these PID control systems. Various advancements are done in auto-tuning these parameters. However, due to the absence in the existing system, which implements the PID control as well as auto-tunes the parameter, this paper aims at constructing a system, which eliminates the hectic process of tuning the PID manually and implementing PID control with ease.